2011
DOI: 10.1111/j.1747-4949.2011.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Fatigue: An Emerging, Critical Issue in Stroke Medicine

Abstract: Poststroke fatigue is a common and disabling condition. However, few studies on or therapeutic trials addressing poststroke fatigue have appeared in the literature. We aimed to review the prevalence, natural course, potential predisposing factors (physiological, psychocognitive, and organic), and pharmacological and nonpharmacological treatments of poststroke fatigue. Using PubMed CINAHL and PsycINFO, we reviewed all the available literature on poststroke fatigue and related issues. The prevalence of poststrok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 92 publications
4
80
0
3
Order By: Relevance
“…5,6 However, post-stroke fatigue has also been found independently of low mood. 7,8 No previous studies have excluded participants with depressive symptoms, allowing fatigue to be investigated independently of this factor. Aside from the link with depression, evidence identifying other factors associated with post-stroke fatigue is limited and often conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, post-stroke fatigue has also been found independently of low mood. 7,8 No previous studies have excluded participants with depressive symptoms, allowing fatigue to be investigated independently of this factor. Aside from the link with depression, evidence identifying other factors associated with post-stroke fatigue is limited and often conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalensi fatigue pada kasus ini di Amerika diperkirakan 36%-77% (Kluger et al, 2013), sedangkan di Korea diperkirakan 23%-75% (Choi-Kwon & Kim, 2011). Menurut NANDA 2015-2017 fatigue merupakan keletihan yang dirasakan secara terus-menerus dan terjadi penurunan kapasistas fisik dan maupun mental.…”
Section: Pendahuluanunclassified
“…Selain itu kasus ini dapat dihubungkan dengan penurunan aktivitas seksual dari penderitanya (Choi-Kwon & Kim, 2011).…”
Section: Pendahuluanunclassified
“…survivors. Fatigue and depression are often problems for stroke patients (Hackett et al, 2005;Choi-Kwon & Kim 2011). Several studies have shown that physical training produced a positive effect on non-physical outcomes like fatigue and depression (Sjosten & Kivela 2006;Blake et al, 2009;Mead et al, 2009).…”
Section: Group Circuit Class Therapy For Stroke Survivors -A Review Omentioning
confidence: 99%